Students' Perspectives on the Implementation of the Kollaboratives Schreiben Model with the PORPE Method in Developing German Writing Skills - Katarina Agustin; Dewi Kartika Ardiyani (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This study explores students’ perspectives on the implementation of the Kollaboratives Schreiben (Collaborative Writing) model integrated with the PORPE method (Predict, Organize, Rehearse, Practice, Evaluate) in enhancing German writing skills among eleventh-grade students at SMA Taruna Nala, Indonesian. Employing a qualitative descriptive approach, the study involved 16 students as participants. Data were collected through open-ended questionnaires focusing on students’ views regarding the combined application of Kollaboratives Schreiben and the PORPE method. The findings reveal that students responded positively to the collaborative aspects of the model, stating that it was enjoyable and supportive in developing writing skills and teamwork. Despite challenges such as limited vocabulary and the extended time required for implementation, the structured steps provided by the PORPE method helped students produce more organized texts.